2019
DOI: 10.1111/1365-2435.13432
|View full text |Cite
|
Sign up to set email alerts
|

Earlier plant growth helps compensate for reduced carbon fixation after 13 years of warming

Abstract: Drylands play a dominant role in global carbon cycling and are particularly vulnerable to increasing temperatures, but our understanding of how dryland ecosystems will respond to climatic change remains notably poor. Considering that the area of drylands is projected to increase by 11%–23% by 2,100, understanding the impacts of warming on the functions and services furnished by these arid and semi‐arid ecosystems has numerous implications. In a unique 13‐year ecosystem warming experiment in a south‐western U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This study was conducted in a semiarid grassland located near Castle Valley, Utah, USA and close to a long-term climate manipulation experiment on the Colroado Plateau (38 • 40 ′ 26.52 ′′ N, 109 • 24 ′ 59.27 ′′ W; Wertin et al, 2015). The site has a history of limited-to no direct anthropogenic impacts prior to establishment of the study and the soils are classified as sandy loam, calcareous, Rizno series (Grand County Soil Survey; Winkler et al, 2019). Air temperature and precipitation values were collected from a weather station located ∼200 m from the collection site ( Figure S1).…”
Section: Study Site and Soil Samplingmentioning
confidence: 99%
“…This study was conducted in a semiarid grassland located near Castle Valley, Utah, USA and close to a long-term climate manipulation experiment on the Colroado Plateau (38 • 40 ′ 26.52 ′′ N, 109 • 24 ′ 59.27 ′′ W; Wertin et al, 2015). The site has a history of limited-to no direct anthropogenic impacts prior to establishment of the study and the soils are classified as sandy loam, calcareous, Rizno series (Grand County Soil Survey; Winkler et al, 2019). Air temperature and precipitation values were collected from a weather station located ∼200 m from the collection site ( Figure S1).…”
Section: Study Site and Soil Samplingmentioning
confidence: 99%
“…Population changes under fluctuating climatic conditions often result from a complex interaction of life history and climatic stresses in which sensitivity to changes strongly affects long-term trajectories (Oostermeijer et al 1994, Conver et al 2017, Winkler et al 2019b. As a result, we expect highly sensitive populations to respond more strongly and positively to periods that favor recruitment and survival but also strongly and negatively to unfavorable periods.…”
Section: Discussionmentioning
confidence: 96%
“…Modeling populations of long-lived perennials is challenging given the time scale at which they respond to change (Morris et al 2008) in addition to the spatial variation in the multitude of biotic and abiotic factors that influence population dynamics (Wright et al 2014, Kroiss andHilleRisLambers 2015). The interaction of spatial and temporal heterogeneity adds further complication to understanding past and predicting future dynamics (Freestone and Inouye 2006, Conlisk et al 2018, Winkler et al 2019a, 2019b.…”
Section: Introductionmentioning
confidence: 99%
“…Although our data point to a shortened B. tectorum growing season with both 2 and 4 • C increases in temperature, the large phenological flexibility we observed suggest warmer conditions could also afford B. tectorum a competitive advantage over the perennial plants it lives amongst if those perennial plants are not able to respond to changing climate as quickly. We did not analyze phenological responses to warming of co-occurring species here, however, previous research in these experiments has shown a dominant native perennial species has experienced dramatic declines in cover in response to warming, potentially enabling B. tectorum to take advantage of this newly opened space and further invade the site (Winkler et al, 2019). Due to the large effect of B. tectorum on native perennials, any climate change effects on the invasive grass could, in turn, affect the success of native plants (Willis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bromus tectorum phenology was assessed in three complementary climate manipulation experiments, which have been described previously (Reed et al, 2012;Zelikova et al, 2012Zelikova et al, , 2013Wertin et al, 2015Wertin et al, , 2017Winkler et al, 2019 Moab, Utah (38.31 N, -109.28 W, 1227 m elevation). Soils at the Moab site are sandy loam, Sheppard series, with a thin petrocalcic layer at a depth of 0.5 m. The soil texture at the site is 92% sand, 2% silt, and 5% clay as assessed by the texture-by-feel method (Salley et al, 2018).…”
Section: Study Locationmentioning
confidence: 99%